The facial reconstruction of a Mesolithic Dog, Muge, Portugal - Moraes, Cicero (2022)
ABSTRACT: This paper presents the facial reconstruction of a Mesolithic dog whose skeleton was recovered from the Muge shell middens (Portugal) in the 19th century. We used the anatomical deformation approach based on a collection of computer tomography images as an attempt to reconstruct the Muge dog's head appearance. We faced a few challenges due to the level of bone displacement and the absence of some cranium anatomical parts, as well as accurate information on soft tissue thickness for modern dogs. This multidisciplinary study combined anatomical, veterinary, zooarchaeological, artistic and graphic aspects to allow for the facial reconstruction of the Muge dog. Albeit an approximation, it confers a recognition to this prehistoric finding.